Where Do Social Inequalities Come From?: Class Divides in Chicana/o-Latina/o Literature - González, Marcial (Radical Teacher, 2015)
There’s no denying that the Occupy movement, aside from everything else it has accomplished since 2011, created ample opportunities in college classrooms for teaching about the super wealthy, or the 1%, and their role in reproducing social and economic inequalities in the United States and around the world. In my own courses, however, I have tried to emphasize to students that there is a marked difference between teaching about “the rich” and teaching about “class.”